Reversible Hydration Composite Films for Evaporative Perspiration Control and Heat Stress Management (Small 14/2022). Issue 14 (7th April 2022) - Yang, Jiachen; Zhang, Xueping; Koh, J. Justin; Deng, Rensheng; Kumarasamy, Saravana; Xu, Yuan Xing; Qu, Hao; Zhang, Songlin; Zhang, Yaoxin; Tan, Swee Ching
Abstract : Personal Protective Equipment The frontline healthcare workers donning personal protective equipment for a prolonged time often face occupational heat strain. In article number 2107636, Xueping Zhang, Swee Ching Tan, and co‐workers address this issue by developing a super‐hygroscopic composite film that absorbs water vapor within the protective suit and enhances sweat evaporation, to create a cooling effect for better thermal comfort.